Pertautan Epistemologi Filsafat dan Tasawuf: Telaah Sistem Pemikiran Abdul Halim Mahmud - Lalu Muchsin Effendi (Ulumuna, 2013)
Islamic Epistemology has long been a centre of Islamic Scholars’ debate. It is apparent in the discourse disputes among mutakallimūn, philosophers, and sufis as well as traditionalists versus modernists. This research hence tries to reveal Abdul Halim Mahmud’s thought which analyzes Tasawuf epistemological system. Preceded by comparative studies, this research focuses on identifying the essence of Tasawuf based on Abdul Halim Mahmud’s analysis. Findings of the research include Qur’an and Hadith become sources of Islamic teachings on Tasawuf epistemological system. Also, God blessing through the process of mushāhadah dan mukāshafah is able to solve metaphysical problems and hence becomes a source of intuitive based knowledge.